2019
DOI: 10.1016/j.jsxm.2019.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Sexual Relationships Study Involving wOmen and meN (PASSION Study)

Abstract: Introduction Sexual satisfaction is believed to decrease during pregnancy; however, the effect of pregnancy on the sexual relationship in a couple is not well studied. Aim To assess for sexual dysfunction in heterosexual couples during pregnancy. Methods We performed a cross-sectional study of heterosexual pregnant women in the third trimester and their cohab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
6
0
3
Order By: Relevance
“…According to the literature, many studies (61.4%) show that the frequency of sexual intercourse during pregnancy is two or less per week. 14,27,34 The decrease in the frequency of sexual intercourse during pregnancy is multifactorial. Pain during coitus (24.51%) is one of the important factors affecting living.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature, many studies (61.4%) show that the frequency of sexual intercourse during pregnancy is two or less per week. 14,27,34 The decrease in the frequency of sexual intercourse during pregnancy is multifactorial. Pain during coitus (24.51%) is one of the important factors affecting living.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Jamali and Mosalanejad 32 (2013) there was no relationship between sexual dysfunction and variables such as education level, maternal age, occupation or parity; Dwarica et al 27 (2019) and Pauleta et al 8 (2010) studies; no relationship was found between sexual function and education level, maternal age and income level. In a study conducted in Turkey, pregnant women living in socio-economic regions, women age, spouse's age, peer education, pregnancy trimester is a statistically significant relationship between women's sexual function subscales with spousal support and frequency of sexual intercourse bulunmuştur.…”
Section: Association Between Socio-demographic Characteristics Of Wom...mentioning
confidence: 94%
See 1 more Smart Citation
“…Em A2, foi investigada a possível relação entre a queda na função sexual e dispareunia. Ela pode ter sido um fator contributivo para as gestantes terem evitado a relação sexual (DWARICA et al, 2019). A dispareunia é qualquer tipo de dor no momento da penetração vaginal.…”
Section: Categoria 3: Dispareunia Como Elemento Impeditivo à Atividad...unclassified
“…Há certa escassez de estudos que abordam a influência do parceiro na sexualidade da gestante e como as alterações sexuais de ambos refletem no relacionamento conjugal durante a gravidez. Além disso, faltam informações sobre a satisfação sexual do homem durante esse período 12 , bem como quais são as consequências dessas alterações para a mulher. Por essa razão, este artigo apresentou como objetivo analisar a influência do parceiro na sexualidade da gestante e como a qualidade da relação conjugal é afetada nesse período.…”
unclassified